ANALISIS AKTIVITAS DENGAN MENGGUNAKAN ACTIVITY BASED COSTING DAN ACTIVITY BASED T DALAM RANGKA PENINGKATAN EFISIENSI DAN LABA - LIE YUNG YUNG (Media Bisnis, 2015)
The research objective is to determine the cause of non-value added activities that cause inefficiency and impact as well as to profit at PT Megatex INDOTAMA . The method of research is field research and library research. Based on the research conducted, it turns out it is known that Cost Management System used is the traditional costing and there are also activities of non-value added so that the company's goal of achieving competitive advantage through cost efficiencies and increased profits are not achieved. Therefore, an analysis activities using the activity -based costing and activity based t. After analyzes, the company should review the fee system is used for this, is overseeing the activities of non-value added that is not too big or operated as efficiently as possible.